Interaction of α‐Synuclein with Phospholipids and the Associated Restructuring of Interfacial Lipid Water: An Interface‐Selective Vibrational Spectroscopic Study. (7th October 2020) - Biswas, Biswajit; Roy, Subhadip; Mondal, Jahur Alam; Singh, Prashant Chandra
Abstract: Interaction of α‐Synuclein (αS) with biological lipids is crucial for the onset of its fibrillation at the cell membrane/water interface. Probed herein is the interaction of αS with membrane‐mimicking lipid monolayer/water interfaces. The results depict that αS interacts negligibly with zwitterionic lipids, but strongly affects the pristine air/water and charged lipid/water interfaces by perturbing the structure and orientation of the interfacial water. The net negative αS (−9 in bulk water; pH 7.4) reorients the water as hydrogen‐up (H‐up) at the air/water interface, and electrostatically interacts with positively charged lipids, making the interface nearly net neutral. αS also interacts with negatively charged lipids: the net H‐up orientation of the interfacial water decreases at the anionic lipid/water interface, revealing a domain‐specific interaction of net negative αS with the negatively charged lipids at the membrane surface. Abstract : Probed herein is the interaction of α‐Synuclein (αS; shown in yellow) with membrane‐mimicking lipid monolayer/water interfaces. αS affects the pristine air/water and charged lipid/water interfaces by perturbing the structure and orientation of the interfacial water. The net negative αS reorients the water as "H‐UP" at the air/water interface and electrostatically interacts with positively charged lipids. αS also interacts with negatively charged lipids upon a change in the orientation of the water.